Influenza DNA vaccine purification using pHEMA cryogel support - Santos, Tiago (2018)
Influenza virus is a huge financial and social burden for health care systems over the world. Currently, traditionalapproaches are not effective in the fight of the epidemy and new alternatives like DNA vaccines have been developed. However, the downstream process of DNA vaccines is a constant challenge in the biotechnology industry. Cryogels has several advantages over traditional supports and have been tested as stationary phase in chromatographic separations. In this work, a method based on poly(2-hydroxyethyl methacrylate) cryogel was used to purify the plasmid NTC7482-41H-VA2 HA, which express the Influenza hemagglutinin gene. For this purpose, the cryogel was synthesized by cryo-polymerization of 2-hydroxyethyl methacrylate and characterized by scanning electron microscopy. The purification of supercoiled isoform of the plasmid NTC7482-41H-VA2 HA from a clarified lysate sample was achieved in a two-step experiment using NaCl and the dynamic binding capacity of pHEMA cryogel was determined. The assessment of DNA vaccine allowed to conclude that the level of contaminants such as proteins, genomic DNA, RNA and endotoxins are in accordance with FDA agency.